KUBUR TEMPAYAN DI SIULAK TENANG, DATARAN TINGGI JAMBI DALAM PERSPEKTIF EKONOMI, SOSIAL, DAN KEPERCAYAAN - Tri Marhaeni S. Budisantosa (Balai Arkeologi Bali, 2015)
Siulak Tenang is a jar burial site amongst the other similar sites located on the highland of Jambi. Researches for burial jar have been done, both in Indonesia and other regions such as Malaysia, Brunei, and Philliphine, so that the result of this research can add new data about jar burial. This writing discusses the data obtained from the excavation in Siulak Tenang in 2014. The artefactual analysis applied methods of specific analysis, quantitative analysis, contextual analysis, and comparative analysis.The discussion reveals that most of the jar burials are single burials except the one covered with a pot. Few burial gift were also found in the forms of pottery vessel and bronze things. It shows that the past Siulak Tenang had involved in maritime trade or exchange network, recocgnized the difference of social status, and believed in life after death.Siulak Tenang merupakan salah satu situs kubur tempayan di dataran tinggi Jambi. Penelitian kubur tempayan telah lama dilakukan, baik di Indonesia maupun wilayah lain, seperti Malaysia, Brunei, dan Filipina, sehingga hasil penelitian ini dapat menambah data baru tentang kubur tempayan. Penelitian ini membahas hasil ekskavasi Situs Siulak Tenang tahun 2014. Analisis artefak menerapkan metode analisis spesifik, analisis kuantitatif, analisis kontekstual, dan analisis komparatif. Hasil penelitian di Situs Siulak Tenang sebagian besar merupakan kubur tempayan tunggal, kecuali satu tempayan yang ditutup dengan periuk, sebagian kecil terdapat benda bekal kubur berupa wadah gerabah dan benda perunggu. Hal tersebut menunjukkan adanya aktivitas perdagangan atau pertukaran, dikenalnya stratifikasi sosial dan kepercayaan akan kehidupan di dunia arwah.